Rhetorical structure and linguistic features of research article abstracts in the humanities: the case of Lithuanian, English, and Russian - Gobekci, Erika (Taikomoji kalbotyra, 2023)
Over the past few decades, research article abstracts have been receiving increased attention of scholars. While abstracts in English have been extensively researched, there are few studies on abstracts in Russian and no studies on abstracts in Lithuanian. This study investigates the rhetorical structure and linguistic features of research article abstracts across different humanities disciplines in Lithuanian, English and Russian. My aim is to detect similarities and differences in abstract structure and corresponding linguistic features within the three different academic writing traditions. I seek to answer the question which writing tradition, the Anglo-Saxon or the Continental, is closer to Lithuanian academic writing. This study employs contrastive qualitative and quantitative analysis and corpus-based methodology. The results highlight aspects of abstract writing that may be relevant for researchers while preparing abstracts of their research articles in these three languages.
Keywords: academic discourse; humanities; research article abstract; rhetorical structure; cross-linguistic research